Investigating the introduction and the robustness of lobbying laws - Crepaz, Michele (Trinity College (Dublin, Ireland). Department of Political Science, 2017)
Lobbying regulations belong to the political realm of ethics, integrity and transparency. They aim at regulating the activity of private actors who are seeking to influence the state. Existent research revealed that initiatives of transparency achieved through these laws help the government to install a level playing field for the participation of interest groups in the policy making process and to prevent cases of corruption. Besides, since these laws shed light over the policy making process, they allow citizens to hold policy makers accountable for their decisions. However, some lobbying laws guarantee higher levels of transparency and accountability than others. The level of transparency and accountability of lobbying regulations is defined as robustness. Previous research on this topic has revealed that provisions in lobbying laws can vary in robustness, that is to say they can be more or less robust. Building upon these studies, my project addresses two main research questions: First, what are the reasons for political systems to introduce lobbying regulations? -And secondly –within political systems that have passed lobbying laws, why are some regulations more robust than others? My study offers two empirical Investigations to answer these questions. First, I explore the adoption of lobbying Laws in EU and OECD countries testing a set of explanations based on theories of political agenda setting, policy diffusion and systems of interest representation. Secondly, I explore the effects of corporatism, political corruption scandals and Partisanship on the robustness of lobbying regulations in the EU, Austria, Ireland and the UK. The empirical analyses are conducted using a mixed-method approach: as far as the adoption of lobbying laws is concerned, I use a quantitative event history analysis of 34 cases in the period between 1995 and 2014; the Determinants of the robustness of lobbying laws, in turn, are investigated in four case studies. This study represents the first comparative investigation of the emergence and the robustness of lobbying laws in contemporary democracies. The quantitative analysis of the adoption of lobbying laws (Chapter 3) suggests that IOs and states with regulations already in place encourage the diffusion of lobbying rules in OECD and EU member states. Neither levels of corporatism nor the media’s attention to scandals appear to be significant predictors of the adoption of lobbying laws. However, scandals influence the legislative activity around lobbying regulations. The results of the analysis suggest that media attention towards episodes of corruption influences the presentation of legislative proposals to regulate lobbying. These proposals, however, fail to become laws. I argue that this represents an expression of ‘symbolic’ politics. The results of the case studies (Chapter 6) of the EU and Austria suggest that systems of interest representation influenced of the levels robustness of the lobbying laws. The results of the investigation conducted in the UK and Ireland suggest that party politics and the saliency of lobbying scandals help to explain different levels of robustness. The results of this investigation can help scholars to better understand the reasons for which states develop transparency legislations and give a deeper insight into the dynamics related to accountability and transparency in the real world of politics.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin